Iklan, Asosiasi Merek, dan Keputusan Pembelian - Tauriana, Dian; Safriliana, Devy (Bina Nusantara University, 2009)
The impact of advertising on brand association has raised many questions among scholars. Some agree that advertising can leverage and help building brand association in consumer’s perspective. Others are against this opinion. However, this research is trying to investigate whether advertising does correlate to brand association that later on impacts on purchase decision making. Data collected by interviewing respondents regarding car purchase in the showroom. The analysis is conducted by using path analysis. From the result, it is figured out that the influence/impact of brand association on purchase decision making is very low. Thus, other element such as advertising and any activities to leverage brand association should be taken into account.